The Effect of AZ61 Content on Mechanical Strength and Surface Hardness of PA6-AZ61 Magnesium Alloy - Tanoto, Yopi Yusuf; Huang, Song-Jeng (Journal of Research Updates in Polymer Science, 2023)
In this study, a Polyamide 6 (PA6)-AZ61 magnesium alloy composite and pure PA6 were fabricated using a compression molding instrument. Both the matrix and reinforcement were prepared in powder form. A planetary ball milling machine was employed to mix the PA6 and AZ61 micro powders. The effects of AZ61 content at different percentage on the final properties of the composite were investigated. X-ray diffraction (XRD) analysis and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS) were employed to verify the uniformity of the mixing process and to confirm the composition of both the raw materials and the composite. The result, relative to pristine PA6, the ultimate tensile strength (UTS) demonstrated a substantial increment of 48.3%, reaching 58 MPa. Whereas the yield strength (YS) exhibited a notable surge to 49.38 MPa, constituting a 52.9% enhancement. Additionally, the PA6-5AZ61 composition achieved the highest microhardness value at 21.162 HV, signifying a remarkable 66.3% augmentation compared to the unalloyed PA6 material. This result suggests that AZ61 has the potential to improve the properties of the matrix material.